Managing sedation in the mechanically ventilated emergency department patient: a clinical review - Clifford L. Freeman; Christopher S. Evans; Tyler W. Barrett (Journal of the American College of Emergency Physicians Open)
Abstract Managing sedation in the ventilated emergency department (ED) patient is increasingly important as critical care unit admissions from EDs increase and hospital crowding results in intubated patients boarding for longer periods. The objectives of this review are 3‐fold; (1) describe the historical perspective of how sedation of the ventilated patient has changed, (2) summarize the most commonly used sedation and analgesic agents, and (3) provide a practical approach to sedation and analgesia in mechanically ventilated ED patients. We searched PubMed using keywords “emergency department post‐intubation sedation,” “emergency department critical care length of stay,” and “sedation in mechanically ventilated patient.” The search results were limited to English language and reviewed for relevance to the subject of interest. Our search resulted in 723 articles that met the criteria for managing sedation in the ventilated ED patient, of which 19 articles were selected and reviewed. Our review of the literature found that the level of sedation and practices of sedation and analgesia in the ED environment have downstream consequences on patient care including overall patient centered outcomes even after the patient has left the ED. It is reasonable to begin with analgesia in isolation, although sedating medications should be used when patients remain uncomfortable and agitated after initial interventions are performed.